1966
DOI: 10.1136/oem.23.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy in Rats Produced by Acrylamide

Abstract: Acrylamide produces ataxia and limb weakness in rats when given in repeated oral doses of 25 100 mg./kg. at various intervals or mixed with the diet in concentrations of 100 to 400 p.p.m. An electrophysiological and histological study of peripheral nerves has been carried out in chronical poisoned rats. In animals with severe clinical abnormalities, motor nerve conduction velocity in the fibr supplying the small muscles of the hind paw was reduced to approximately 80% of the control value. Histologically, dege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
89
1
1

Year Published

1968
1968
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(100 citation statements)
references
References 13 publications
9
89
1
1
Order By: Relevance
“…Acrylamide ingestion robustly causes a retrograde pattern of sensorimotor axonal loss in rodents, and we and others have previously shown that the extent of this distal axonal loss closely correlates with the severity of hind limb grip weakness (4,21,23,27). In subsequent ex vivo experiments, we noted that relatively low doses of the NO donors SNAP and NOR3 prevented axonal degeneration in DRG cultures induced by acrylamide.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Acrylamide ingestion robustly causes a retrograde pattern of sensorimotor axonal loss in rodents, and we and others have previously shown that the extent of this distal axonal loss closely correlates with the severity of hind limb grip weakness (4,21,23,27). In subsequent ex vivo experiments, we noted that relatively low doses of the NO donors SNAP and NOR3 prevented axonal degeneration in DRG cultures induced by acrylamide.…”
Section: Discussionmentioning
confidence: 87%
“…Acrylamide-induced peripheral neuropathy is a well-established, reproducible rodent model of distal axonal degeneration (21). Acrylamide is known to interfere with slow axonal transport (22).…”
Section: Resultsmentioning
confidence: 99%
“…This chemical appears to damage nerve tissue selectively and has been known for some time to cause peripheral neuropathies (Fullerton and Barnes, 1966;Pleasure et al, 1970;Schaumberg et al, 1974). More recently central nervous system involvement in acrylamide poisoning has also been reported in experimental animals (Ghetti et al, 1973;Gipon et al, 1977;Schotman et al, 1978;Schaumburg and Spencer, 1978).…”
mentioning
confidence: 99%
“…These include pupil dilation, excess salivation, distension of the urinary bladder, and tremor (Fullerton and Barnes, 1966;Thoman et al, 1974).…”
mentioning
confidence: 99%
“…The peripheral nervous system is clearly damaged and both human and experimentally-induced neuropathies have been described (Tilson et al 1979;Fullerton and Barnes 1966;Fujita et al 1961). Central nervous system malfunction is also reported for experimental animals and humans (Igisu et al 1975;Spencer and Schaumburg 1974).…”
Section: Introductionmentioning
confidence: 99%